THE GIRL-CHILD: A SOCIOLOGICAL VIEW ON THE PROBLEMS OF GIRL-CHILD EDUCATION IN NIGERIA - T. Alabi; M. Bahah; S.O. Alabi (European Scientific Journal, ESJ, 2014)
Today’s girls are tomorrow’s women; the differential treatment of girls and boys can hardly be separated from the preferential treatment of men to women in our society. Being born and growing up as a girl in a developing society like Nigeria is almost like a curse due to contempt and ignominy treatment received from the family, the school and the society at large. The cumulative effects of these discriminatory, exploitative and unjust treatments have had profound negative impacts on education opportunities available to girl-children. This paper therefore examined the general problems facing a girl-child and the peculiar challenges facing their education opportunities in Nigeria. Information used by the authors were collected from published articles, text and internet sources. The paper revealed some the cultural and traditional beliefs and practices in Nigeria which constitute major barriers to the education opportunities of girl-children. The authors concluded by suggesting some ways of enhancing girl-child education through holistic approach.